Enhanced Dynamic Response of DC-AC Converters in Shipboard Microgrids Using Non-linear PI Controller - Naghash, Reza; Hassan, Mustafa Alrayah; Kauhaniemi, Kimmo; Laaksonen, Hannu (IEEE, 2025)
This work presents a non-linear digital PI controller for DC-AC converters in shipboard microgrids (SMG) with hybrid energy storage systems (HESS), including battery and supercapacitor. The HESS power converters in SMG need fast and well-tuned dynamic response to ensure reliable operation in their distinctive load characteristics such as large variations in line voltage, load changes, and high degree of non-linearity. Conventional PI controllers prove their performance in most cases, however, due to their linear behaviour, they may fail to maintain all the control system parameters at desired ranges over the large and fast transients. To address this issue, a case study based on real mission profile of a hybrid ship is considered, and a non-linear PI controller with variable gains for different error values based on non-linear functions is introduced. Stability analysis based on frequency-domain and bode diagrams provides the improvement in dynamic response, and it is verified by simulation and controller hardware-in-the-loop (CHIL) tests.
Keywords: DC-AC Converters; Non-linear PI Controller; Adaptive Control; Fast Dynamic Response; CHIL Test; Shipboard Microgrids; Hybrid Energy Storage Systems; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkötekniikka|en=Electrical Engineering|